Clinicopathological Study on Anal Cryptitis - Ieda, H.; Kawase, K.; Miura, Y.; Miyata, M.; Ohta, A. (Nippon Daicho Komonbyo Gakkai Zasshi, 2000)
To elucidate clinical features of anal cryptitis, 102 patients with this disease treated in our clinic from July 1995 to June 1996 were reviewed. There were 69 males and 33 females aged 14 to 85 years. Mild to moderate anal pain, usually not related to defecation, was the chief complaint and especially appeared when the patient was in the sitting position.The duration of the symptoms varied. Of the 102 subjects, 28 had a combined anal fissure, whereas no patients had a combined anal fistula. The anal crypt with inflammation was deformed and compression pain was found on digital examination. Cryptitis occurred predominantly at the crypt located at the posterior wall of the anus. Histologically, lymphocyte infiltration without destruction of the anal gland was characteristic of cryptitis, indicating that the disease is a mild chronic inflammation. A conservative therapy with medication was a first choice of treatment. Cryptectomy was indicated in patients with an intractable disease. In conclusion, anal cryptitis is a mild chronic inflammatory disease, rarely resulting in anal fistula or abscess. Although the pathogenesis is still unknown, anal cryptitis should be recognized as a clinical entity of anal diseases from both the clinical and pathological viewpoints.